Gaetano Martino e il Comitato dei Tre Saggi - villani angela (2018)
This paper aims at analysing the contribution of the former Italian Foreign Minister, Gaetano Martino, to the Committee of the Three Wise Men, established by the North Atlantic Council in May 1956 in order to suggest the ways and means to widen and improve the cooperation among Member States in non-military sectors. The need for reflection on this issue, already dealt with by the Commission on the Atlantic Community between 1951 and 1952, was linked both with the evolution of the East-West confrontation during the years of coexistence and with the breaking point that transatlantic relations experienced during the Suez Crisis. In this framework Gaetano Martino, a Liberal who led the Italian Foreign Ministry from 1954 to 1957, expressed the need to rethink the Atlantic Alliance according to the new dynamism of Italian foreign policy. He thus acted in continuity with the pro-western choice the country had made after the Second World War and with the initiatives on non-military cooperation within NATO that the previous Italian governments had carried out. The Report of the Committee of the Three Wise Men stressed the crucial importance of shaping a multi-level dimension of security that was to be confirmed as a task for NATO and for the entire international community, after the end of the Cold War.